Educational Outcomes of Adolescents Participating in Specialist Sport Programs in Low SES Areas of Western Australia: A Mixed Methods Study - O'Hara, Eibhlish; Harms, Craig; Ma'ayah, Fadi; Speelman, Craig (Frontiers in Psychology, 2021)
Specialist Sport Programs (SSPs) are an underexamined activity that combines the best features of two different contexts for adolescent development: a sporting program and a secondary school. A mixed-methods study was conducted to determine the influence of participation in SSPs on the educational outcomes of lower secondary students in Western Australia. The results demonstrated a significant improvement in specialist students’ mean grade for Mathematics over the course of a year, while their mean grade for all other subjects, and their level of engagement with school, remained stable over the same period of time. Semi-structured interviews were also conducted with key stakeholders (e.g., specialist students and their parents, as well as teachers and graduates of the SSPs). Overall, the participants felt that SSPs had a positive influence on students’ engagement with school, and that this engagement had a positive impact on their academic achievement. Taken together, the results of this research suggest that there is a role for SSPs in promoting positive educational outcomes for lower secondary students attending public schools located in low SES areas.